2016
DOI: 10.1177/875687051603500402
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Special Education versus Regular Education Decisions of Future Teachers in the Rural Midwest

Abstract: Persistent shortages of special education teachers, particularly in rural areas, exist across the country. This study assessed the openness of teacher candidates enrolled in an introductory education course at two rural Midwest universities to a special education career path. Survey findings confirmed that work or volunteer experience involving people with special needs is a significant predictor of choosing special education as a career path. Findings also revealed that not all students who have experience wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Although the survey method of this study, using an invalidated instrument with a small, non-randomized sample prevents generalizations across the general population, the information in this study contributes a preliminary understanding not only about why individuals choose special education but also the impact of experiences with individuals with disabilities as an influential factor in making that decision. This finding is consistent with other researchers who have also concluded that experiences with individuals with disabilities as a predictor in choosing special education as a career [2,18] . The information obtained in this study repeatedly identified prior experiences as a contributing factor for choosing to teach students with disabilities.…”
Section: Discussionsupporting
confidence: 93%
“…Although the survey method of this study, using an invalidated instrument with a small, non-randomized sample prevents generalizations across the general population, the information in this study contributes a preliminary understanding not only about why individuals choose special education but also the impact of experiences with individuals with disabilities as an influential factor in making that decision. This finding is consistent with other researchers who have also concluded that experiences with individuals with disabilities as a predictor in choosing special education as a career [2,18] . The information obtained in this study repeatedly identified prior experiences as a contributing factor for choosing to teach students with disabilities.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, continued research to identify factors related to choosing a career in special education is needed to explore methods to attract and recruit more individuals to the field. Additionally, DeSutter and LeMire (2016) recommended that research be conducted to investigate the types of experiences that are most influential in deciding to pursue a career in special education. As such, the purpose of this study is to examine who is choosing to become special educators and what experiences influenced their decision.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In the past decade, only five research studies, conducted in the United States, have investigated factors that influence an individual’s interest to work primarily in special education. The participants in two of those studies were comprised of in‐service special education teachers (Fish and Stephens, 2010; Stephens and Fish, 2010), whereas the participants in the remaining three studies included early‐career undergraduate education majors (DeSutter and LeMire, 2016; Reeves, et al, 2018; Zhang et al, 2014).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Although our focus is on intervention support for practicing special and general educators who serve students with disabilities, three points from the personnel preparation literature are instructive for the current discussion. First, it is critical to establish schooluniversity partnerships as rural schools look to universities to help recruit, prepare, and sustain their workforce (DeSutter & LeMire, 2016;Hoppey, 2016;Williams et al, 2002). This includes providing teacher education candidates with clinically rich training experiences, opportunities to experience the activities and responsibilities involved in being a special educator in rural settings and developing preservice teachers' knowledge and skills in the use and delivery of EBPs.…”
Section: Special Education Support Needs In Rural Communitiesmentioning
confidence: 99%